Случайные движения бистабильного осциллятора с периодическим воздействием - Никитина, Н.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The influence of a local loading on the stressed state of hollow three-layered cylinders corrugated in the cross section and with transversally isotropic middle layer is investigated on the basis of the method of approximation of functions by discrete Fourier series. Distributions of the fields of displacements and stresses are presented.